Response of irrigated oil palm in the nursery and the field to nitrogen, phosphorus and potassium fertilizers - Arifin, Izwanizam (2018)
Nutrient demand for oil palm is determined by the potential yield, which is varies according to genotype, soil, palm age and environment factor. Moisture stress having a strong influence on oil palm growth and development. Irrigation project was carried out to study the growth performance and yield response of oil palm to irrigation. Therefore, this study highlight the results the major plants nutrients requirements for an oil palm and the strategies to optimize the usage of fertilizer in oil palm under irrigation system. An experiment was laid out at the Oil Palm Nursery, Felda Agricultural Services Tun Razak, Jerantut, Pahang, Malaysia (3° 52' 55" N, 102° 43' 41" E) and FASSB Tembangau 9 Estate (03°00’59.5”N, Longitude 102°28’48.5”E). Experiment of 33 NPK factorial fertilizer trials were conducted for oil palm seedlings in nursery and mature D × P palms planted in the year 2000 under irrigation condition. The trial was conducted on Gong chenak series (Aquic kandiudults) (Soil Survey Staff, 2010). The following rates were used: 0, 112 and 224 g per seedling per year for N (Ammonium sulphate); 0, 71 and 142 g per seedling per year for P (Christmas island rock phosphate); and 0, 34 and 68 g per seedling per year for K (Muriate of potash). The N and K rates tested for mature oil palm were at 0, 4 and 8 kg per palm per year, while P rate tested at 0, 2 and 4 kg per palm per year. Field operation and maintenance of trial plot was as per normal estate practices. Experiment on the NPK factorial trial on oil palm seedling showed that there is important aspect of the need for applying the adequate rate of N fertilizer rather than P and K fertilizer in order to optimize the nutrient uptake. In the absence of N fertilizer, N foliar nutrient status (1.78%), girth size (5.1 cm), seedling height (51.4 cm) and frond length (36.6 cm) was significantly the lowest. The best combination rate of fertilizer for optimum seedling growth was N1P1K1 (112 g SOA, 71 g CIPR and 34 g MOP). Results over 7 years on mature palm showed that the palms treated with complete NPK fertilizer (N1P1K1 and N2P2K2) able to produce average FFB yield at 26.50 – 26.69 t/ha, and much higher by 3.60 – 3.80 t/ha (15-17%) as compared to the plot without fertilizer (N0P0K0) at 22.90 t/ha. However, the treatments plot with the lowest yields were N0P2K0, & N0P0K1 at 21.10 t/ha & 21.12 t/ha, respectively. The study also indicated that palm growth and foliar nutrient status showed a significant response to N manuring were recorded throughout the period of the treatment. Unlike N, no significant responses to P and K fertilizer were recorded. Fertilizer rate at N1P1K1 is the best rate to maintain optimum palm growth (particularly estimated LAI and dry frond weight), yield response and foliar nutrient status.